Archers from Rag-i Bibi. Notes on the equipment depicted on Rag-i Bibi relief (Northern Afghanistan) - SKUPNIEWICZ, Patryk (Historia i Świat, 2022)
The rock relief discovered in Rag-e Bibi in Northern Afghanistan in 2002 remains an archaeological sensation. The archery equipment depicted there has not yet been studied. The article describes the bow cases combined with quivers and associates them with the same type of kit popular in Eurasia related with spread of the recurved bows with stiff bone or horn extensions of Xiong Nu/Hunnictype. This type of bows replaced shorter 'Scythian' type of bows in 1st-2nd century CE. The integrated bow case and quiver went out of use soon before the rise of the Sasanians therefore Rag-e Bibi cannot be linked with this dynastic art, based also on the depicted elements of material culture, as well as on stylistic grounds.